Evaluation of Eye Findings in Fibromyalgia Patients - Ahmet Karakoyun; Erdoğan Yaşar; Uğur Gürlevik; Yalkın Çalık (Galenos Yayinevi, 2019)
Objective:Fibromyalgia (FM) is a rheumatic disease which exactly unknown etiology, causes widespread body pain. In FM patients, a large variety of ocular findings, especially dry eye, occur with and without other rheumatic diseases. These ocular findings may be the first findings to warn the clinician for diagnosis in rheumatic diseases. The aim of this study is to evaluate the eye findings as clinically in patients with FM.Materials and Methods:The patients of those between the ages of 18-75, who were admitted to the Aksaray University Training and Research Hospital, Physical Medicine and Rehabilitation Polyclinic and diagnosed with FM, and then examined in the Ophthalmology Polyclinic, were included in the study. Patients' files were reviewed retrospectively. The clinical diagnosis, socio-demographic characteristics, ocular examination findings, history, family history and the results of the treatments were recorded. Those who had undergone eye surgery, rheumatologic disease, diabetic retinopathy, glaucoma, systemic infection, autoimmune disease, cerebrovascular disease, major depression, abnormal laboratory values, and history of malignancy, were not included in the study. The diagnosis of FM was determined according to the American College of Rheumatology updated in 2016.Results:The files of 94 patients who met the appropriate criteria were included in the study. The mean age of the patients was 38.2 (18-75), and 80 (85%) were female and 14 (15%) were male. According to the ocular findings, 57 patients (57.4%) had eye pain, 28.2% had redness, 26.9% had burning-stinging, 15.1% had turbidity, 6.3% had burring, and 3.7% had itching. Among the causes of eye pain were 49.1% dry eye, 24.6% refractive failure, 12.3% blepharitis, and 3.5% allergy, while no cause was found in 10.5%.Conclusion:In our study; it was detected that the patients with FM have a large extent of eye pain, and the most important cause of the eye pain was dry eye. The result of study shows that patients with FM may be accompanied by various ocular findings in addition to chronic widespread body pain and multidisciplinary approach is important in chronic diseases such as FM.